PENGARUH KETAHANAN BETON ASPAL (AC-BC) YANG MENGGUNAKAN ASBUTON BUTIR TIPE 5/20 TERHADAP AIR LAUT DITINJAU DARI KARAKTERISTIK MEKANIS DAN DURABILITASNYA - Djalante, Susanti (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2011)
Provinci South East Sulawesi has the seasore areas bigger than the land areas. In Kendari City, some of the major flexible pavement roads which develoved all along the beach were often flooded by sea water. To protect the destruction of flexible pavement from sea water, using much asphalt is essential in mixture. One of the alternative materials to decrease of using asphalt are to use Asbuton Butir (BRA) which is the deposit about 677 ton millions in Provinci of South East Sulawesi particulary in Button. Regarding to these phenomena, it is important to provide a study the effects of Asbuton Butir (BRA) about the sea water resistance in mechanical characteristic of Asphalt Concrete.The method of the research was using Asbuton Butir that had variation 0%, 50 % and 100% in mixture AC-WC. The first method found the Optimum Asphalt Content (OAC) for each various asbuton butir. The second method aimed to determine the value of Marshall in Optimum Asphalt Content (OAC) which got to discover density, VITM, VFWA, VMA , stability, flow, MQ, IRS standard, IRS modification and Durability Indeks at the immersion time 24 hours, 72 hours and 120 hours.In conclusion, the more many asbuton butir was in AC-BC mixture, the higher value of stability and durability was in AC-BC mixture at the immersion 24 hours, 72 hours and 120 hour in sea water.